Cosmopolitan Lives on the Cusp of Empire : Interfaith, Cross-Cultural and Transnational Networks, 1860-1950 /: Interfaith, Cross-Cultural and Transnational Networks, 1860-1950. (2017) - Haggis, Jane; Midgley, Clare; Allen, Margaret; Paisley, Fiona
No abstract available